2012
DOI: 10.1161/circulationaha.111.065490
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Family History and Coronary Heart Disease Death Across Long-Term Follow-Up in Men

Abstract: Background Family history of coronary heart disease (CHD) has been well studied as an independent risk factor for CHD events in the short term (<10 years). However, data are sparse on the association between family history and risk for CHD across long-term follow-up. Methods and Results We included 49 255 men from the Cooper Center Longitudinal Study. Premature family history of CHD was defined as the presence of angina, myocardial infarction, angioplasty, or bypass surgery in a relative <50 years of age. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 49 publications
4
72
0
9
Order By: Relevance
“…For example, individuals with a family history of diabetes [28] or heart attack personally experienced the stress of managing these serious illnesses [29,30] as well as the wide range of their complications. Although this survey included a large diverse sample of English, Spanish or Korean speaking adults, the findings are similar to previous study results that included only English speaking samples [28,31]. The relationship between BMI and increased perceived risk of diabetes and heart attack has led to the recent broad public campaigns against the obesity epidemic in the United States.…”
Section: Discussionsupporting
confidence: 80%
“…For example, individuals with a family history of diabetes [28] or heart attack personally experienced the stress of managing these serious illnesses [29,30] as well as the wide range of their complications. Although this survey included a large diverse sample of English, Spanish or Korean speaking adults, the findings are similar to previous study results that included only English speaking samples [28,31]. The relationship between BMI and increased perceived risk of diabetes and heart attack has led to the recent broad public campaigns against the obesity epidemic in the United States.…”
Section: Discussionsupporting
confidence: 80%
“…71 A positive family history of premature CV death is associated with an increased risk of early and lifetime CVD. 74 In the few studies that simultaneously assessed and reported the effects of family history and genetic scores, family history remained significantly associated with the incidence of CVD after adjusting for the genetic scores. 75,76 Limited data exist regarding the ability of family history to improve the prediction of CVD a Blood pressure <140/90 mmHg is the general target.…”
Section: Other Risk Markers 241 Family History/(epi)geneticsmentioning
confidence: 99%
“…The important role of genetic factors in atherosclerosis has been clearly demonstrated in numerous studies, including prospective studies of twins, families and cohorts [24], and genome-wide association studies (GWAS) [57]. Apart from rare cases of Mendelian inheritance that are caused by missense or nonsense mutations with large effect, the vast majority of coronary heart disease is complex, probably involving many genes of small effect [8].…”
Section: Introductionmentioning
confidence: 99%